Evaluation of gravel for concrete and road aggregates, Rapti River, Central Nepal Sub-Himalaya - Maharjan, Surendra; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2008)
Several local mining sites of sand and gravel have been operating for decades in the Rapti River. River gravels are consumed in Hetauda, Narayanghad and areas in India near the border between Nepal and India. Until now little known about consumers concerning about quality of gravel. The present study was carried out to evaluate quality of river gravel to know its suitability for aggregate (raw material for concrete and road). The samples of river gravel were analysed for petrographic, physical, mechanical and chemical properties. Samples were categorised as quartzite group, carbonate group and granite group according to British Standard Institution (BSI). Among these, samples of quartzite group were found dominant. Image analysis of gravel showed that clasts were well graded. The majority of the samples had rounded, high sphericity and oblate triaxial clasts. The surface texture of clasts was rough to smooth. In terms of shape, workability of gravel was satisfactory. Gravel samples possessed low water absorption value (0.69 to 1.12%) and low effective porosity. Dry density of samples ranged from 2460 to 2680 kg/m3. Aggregate impact values of samples (14.2 to 16.1%) showed good soundness. Los Angeles abrasion test also showed consistent hardness of each of the samples as uniformity factor did not exceed 0.2. Magnesium sulphate values ranged between 4.46% and 7.29% suggesting good resistance against chemical weathering and frosting. Comparing with the existing Nepal Standard, British Standard and American Standard of Testing Material, the studied samples were suitable for concrete and road aggregates.   doi: 10.3126/bdg.v10i0.1425      Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 99-106